Pembelajaran Sejarah Bermuatan Sejarah Lokal - Yuhardi Yuhardi; Destel Meri (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
This study aims to (1). Describe the local history lesson plan; (2). Describe the process of learning local history; (3). Analyzing obstacles in the local history learning process. The research method uses qualitative research methods with a case study at SMAN 1 Situjuah Limo Nagari. The results showed that the learning planning was made by the teacher himself, the history learning process was not optimal, the students' lack of readiness in dealing with the learning process carried out outside the classroom, the obstacles faced by the teacher in carrying out local history learning were the distance that was too far from the school to the local historical location. The conclusion of this study is that in learning planning it is necessary to design Student Worksheets (LKS) for additional information so that activities can be carried out properly. Local learning makes students more interested in learning history because students interact directly in real life. However, time and transportation are one of the obstacles in learning local history. Keywords: History Learning, Local History.